2009
DOI: 10.1097/gme.0b013e3181a7fb1e
|View full text |Cite
|
Sign up to set email alerts
|

The effects of bazedoxifene on mammographic breast density in postmenopausal women with osteoporosis

Abstract: Treatment with bazedoxifene for 2 years did not affect age-related changes in breast density in this population of postmenopausal women with osteoporosis. The changes in breast density with bazedoxifene 20 or 40 mg were similar to those with raloxifene 60 mg or placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 20 publications
1
40
1
Order By: Relevance
“…Previous clinical studies have shown no evidence of endometrial or breast stimulation in postmenopausal women treated with bazedoxifene for up to 3 years [30][31][32]. In the current study, the incidences of breast cancer, breast cysts, and fibrocystic breast disease with bazedoxifene 20 and 40/ 20 mg were not different than with placebo after 5 years.…”
Section: Discussioncontrasting
confidence: 68%
“…Previous clinical studies have shown no evidence of endometrial or breast stimulation in postmenopausal women treated with bazedoxifene for up to 3 years [30][31][32]. In the current study, the incidences of breast cancer, breast cysts, and fibrocystic breast disease with bazedoxifene 20 and 40/ 20 mg were not different than with placebo after 5 years.…”
Section: Discussioncontrasting
confidence: 68%
“…There was a lower incidence of fibrocystic breast disease with BZA 20 or 40 mg compared with PBO or RLX 60 mg (0.3% for BZA 20 mg, 0.2% for BZA 40 mg, 0.5% for PBO, and 0.8% for RLX 60 mg; overall p ¼ 0.038) [31,32]. A retrospective, ancillary study showed that changes in mammographic breast density at 2 years with BZA 20 and 40 mg were not significantly different from those with PBO or RLX 60 mg [33].…”
Section: Selective Estrogen Receptor Medulators (Serms)mentioning
confidence: 93%
“…It appears that this SERM does not stimulate but rather antagonizes endometrial growth in postmenopausal women (Ronkin et al, 2005). Other clinical trials revealed that bazedoxifene treatment prevents bone loss and reduces bone turnover with similar efficacy to raloxifene in postmenopausal women who have normal-to-low BMD without increasing mammographic breast density, the incidence of hot flashes Silverman et al, 2008Silverman et al, , 2012Archer et al, 2009;Harvey et al, 2009;Kanis et al, 2009;Pinkerton et al, 2009a;Christiansen et al, 2010;Bachmann et al, 2011;de Villiers et al, 2011;Xu et al, 2011). Bazedoxifene also displays efficacy for treating vasomotor symptoms and preventing endometrial hyperplasia in postmenopausal women Pinkerton et al, 2009b).…”
Section: Nuclear Receptors and Their Selective Modulatorsmentioning
confidence: 99%